Beyond IQ: Why Emotional Intelligence is the Key to Exceptional Leadership - Ridho, Ali (Universitas Syiah Kuala, 2024)
This study explores the critical role of emotional intelligence (EI) in effective leadership, highlighting why EI is a more significant predictor of exceptional leadership success than IQ alone. Using a qualitative approach, this research synthesizes insights from interviews, case studies, and thematic analysis of leadership behaviors in various organizational contexts. Findings reveal that emotionally intelligent leaders foster higher levels of team cohesion, adaptability, and motivation, all of which contribute to improved organizational performance. Unlike traditional measures of intelligence, EI encompasses self-awareness, empathy, emotional regulation, and social skills, allowing leaders to navigate complex interpersonal dynamics and respond effectively to the needs of their team. The analysis also underscores the importance of EI in conflict resolution and resilience, especially in challenging environments where cognitive intelligence alone may fall short. This study highlights that while IQ remains valuable for analytical tasks, EI equips leaders with the skills necessary for inspirational leadership and long-term team engagement. The research suggests that organizations aiming to cultivate exceptional leadership should prioritize EI development through targeted training and support programs. These findings provide a comprehensive understanding of EI's impact on leadership effectiveness and underscore its importance as a core competency for modern leaders.